PERJANJIAN BAKU MENGENAI SYARAT DAN KETENTUAN PENGGUNAAN LAYANAN SITUS E-COMMERCE BLIBLI - Syifa Putri Darmaeni (2023)
In the current era of digitalization, Many business actors include standard clauses in their business agreements without considering consumer rights and pour them into a standard agreement so that consumers cannot negotiate on this matter, such as in the terms and conditions of use of the Blibli website/application service. The laws and regulations that govern standard clauses in websites/applications include Consumer Protection Act No. 8 of 1999, which forbids standard provisions that harm customers in an agreement. Based on this, the purpose of this research is to determine and analyze whether the clauses in the Blibli standard agreement are in accordance with those regulated in Law Number 8 of 1999 concerning Consumer Protection, as well as the legal ramifications if the Blibli standard agreement violates the provisions regarding standard clauses in Law Number 8 of 1999 concerning Consumer Protection. The method used in the research is the normative juridical method with a statutory approach. Through this research, it is known that there are various standard clauses that are contrary to the Consumer Protection Law Number 8 of 1999, so that they have the potential to cause harm to consumers. As for the legal consequences of any standard clauses stipulated by business actors that are contrary to Law Number 8 of 1999 concerning Consumer Protection, the agreement is considered null and void.